Corporate Characteristics and Tax Avoidance: Empirical Evidence from Indonesia - Yuli Soesetio (Kirana Publisher (KNPub), 2025)
This study investigates the effect of profitability (ROA), leverage (DER), firm size (SIZE), and managerial ownership (MNGR) on tax avoidance, measured by the effective tax rate (ETR), in companies listed on the Indonesia Stock Exchange. Using a quantitative approach with secondary data from annual reports, the analysis employs moderated regression analysis (MRA) to test both direct and moderating effects. The results show that profitability and firm size have a negative and significant effect on ETR, indicating that highly profitable and larger firms are more likely to engage in tax avoidance. In contrast, leverage has a positive and significant effect on ETR, suggesting that highly leveraged firms tend to reduce tax avoidance, potentially due to creditor monitoring and financial stability concerns. Managerial ownership does not directly affect ETR, but it strengthens the negative relationship between profitability and ETR, supporting the agency theory perspective that managerial equity participation enhances incentives for tax minimization. These findings contribute to the literature by providing new evidence from an emerging market context and offer practical implications for policymakers and regulators in improving tax compliance and corporate governance.